(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: Although interest in the environmental field falls within the field of natural sciences, given the division of knowledge fields between what concerns man and what concerns nature; Due to the difference in its handling of topics, neither in terms of epistemological starting points, nor in terms of the methods used, however, the founders of sociology were aware of the influence of the natural aspect in man and the influence of the first by the action of the second, even if they did not give it sufficient importance in line with the boundaries that were under formation between the various sciences, and in submission to the prevailing epistemological frameworks and in line with what was required by the prevailing social requirements, and this is what we will address in detail in our article. Keywords: environment, sociological research